METAFORA DALAM ANTALOGI PUISI MASIH ADA WAKTU KETIKA SENJA KARYA SUMIYATI & KHAIDAR NAUFAL PASINGSINGAN - Ulfatus Saadahtur Rohmah; Rawinda Fitrotul Mualafina; Zainal Arifin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the use of metaphor in the poetry anthology Masih Ada Waktu Ketika Senja by Sumiyati and Khaidar Naufal Pasingsingan. The research employs a descriptive qualitative approach with observation and note-taking techniques for data collection. The data source consists of 10 poems selected from 46 poems in the anthology through purposive sampling. Data were analyzed using an informal method by presenting the findings descriptively. The results show that various types of metaphors are found in the anthology, namely direct comparison metaphors without comparative markers, metaphors based on the S.P.O. (Subject, Predicate, Object) language function pattern, dead metaphors, and live metaphors. Direct comparison metaphors appear in expressions such as “the solution of the night has been dissolved by time” and “I want to throw that pen into the bin of imagination.” Metaphors based on language function patterns are found in the subject, object, and predicate elements that contribute to the construction of poetic meaning. Dead metaphors are represented by expressions that have become common in everyday language, such as “nuansa lara” (atmosphere of sorrow), “makan hati” (heartache), and “beban derita” (burden of suffering). Meanwhile, live metaphors are found in expressions that remain fresh, creative, and open to interpretation, such as “raindrops interpret feelings” and “the bin of imagination.” The findings indicate that metaphors play an important role in enriching meaning, enhancing aesthetic value, and conveying the poet's inner experiences more profoundly.